Readers’ Engagement with Virginia Woolf’s Mrs Dalloway: From Knowing about Death to the Experience of Finitude - Sopčák, Paul; Kuiken, Don (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2012)
This paper investigates readers’ experience of Virginia Woolf’s Mrs Dalloway, focusing on the themes of death and finitude. In close comparative reading, we first argue that certain passages of the novel effectively explicate Heidegger’s discussion of “thrownness,” “anxiety,” the “uncanny,” the “call of conscience,” and “Being-towards-death.” We then report an empirical study of 46 readers’ comments on passages from Mrs Dalloway that they found striking or evocative. A combination of qualitative and quantitative analyses revealed that a form of enactive and expressive attunement leads some readers to an existential engagement with the text that involves a form of ontological reflection on finitude. We draw on phenomenology (Husserl, Heidegger, Merleau-Ponty) to articulate several distinct reading profiles, emphasizing their relationship to what we call “existential reading.”